Tudor Vladimirescu’s revolution, 200 years (Confluenţe Bibliologice, 2022)
The article contains information about the appearance of postage stamp issues entitled: ,,Tudor Vladimirescu’s Revolution, 200 years”, dedicated to a historical moment and an exceptional personality, emblematic figure for the history of Wallachia, from the beginning of the 19th century, Tudor Vladimirescu (1780-1821) who was the leader of the Revolution of 1821, of the Pandurs and lord of Wallachia.
Keywords: postage stamps; historical personality